Money and Trade in Our World - Shelly Buchanan (Westminster, United States Teacher Created Materials, Inc, 2013)
People all over the world trade and buy from each other! This nonfiction book will teach young readers the various services and goods that countries around the world provide. Readers will also be exposed to the different forms of money, such as yen and pesos, and the difference between wants and needs. Colorful images, supporting text, a glossary, table of contents, and index all work together to help readers better understand the content and be fully engaged from cover to cover.